Sepsis mimicking thyroid storm in a patient with methimazole-induced agranulocytosis. (16th July 2013) - Rayner, Samuel G; Hosseini, Faegheh; Adedipe, Adeyinka A
Abstract : Agranulocytosis is a rare yet life-threatening complication of methimazole therapy for hyperthyroidism. We present the case of a 37-year-old female recently started on methimazole for hyperthyroidism who presented to our facility for evaluation of suspected thyroid storm. In addition to having abnormal thyroid indices, she was noted to have an odontogenic abscess, and was septic with profound neutropenia. Her symptoms resolved quickly following incision and drainage of her abscess and treatment with broad-spectrum antibiotics. Her neutrophil count improved significantly following cessation of methimazole and administration of granulocyte colony-stimulating factor. Diagnosis was initially confounded by the similarity between symptoms of early sepsis and those of thyroid storm. This case report discusses the factors leading to diagnostic delay and highlights the dangerous manifestations of neutropenia in patients on methimazole therapy.